Non‐Hodgkin lymphoma after treatment for classical Hodgkin lymphoma: a report from the German Hodgkin Study Group. (24th January 2021) - Eichenauer, Dennis A.; Müller, Horst; Elger, Leonard; Goergen, Helen; Fuchs, Michael; Kreissl, Stefanie; Böll, Boris; Diehl, Volker; von Tresckow, Bastian; Borchmann, Peter; Engert, Andreas
Summary: Data on non‐Hodgkin lymphoma (NHL) after classical Hodgkin lymphoma (cHL) are scarce. We therefore performed a retrospective analysis comprising 11·841 cHL patients who had first‐line treatment within the randomized German Hodgkin Study Group (GHSG) HD7–HD15 studies. After a median follow‐up of 106 months, 175 patients (1·5%) had developed NHL. The median time to NHL was 44 months, the median age at NHL diagnosis was 54 years. The five‐year event‐free survival and overall survival estimates from the diagnosis of NHL were 36·9% and 44·2%, respectively. Thus, NHL after cHL is a rare event primarily affecting older individuals and often resulting in the patient´s death.